2020
DOI: 10.1007/s10856-020-06462-x
|View full text |Cite
|
Sign up to set email alerts
|

Decellularized tissue-engineered heart valves calcification: what do animal and clinical studies tell us?

Abstract: Cardiovascular diseases are the first cause of death worldwide. Among different heart malfunctions, heart valve failure due to calcification is still a challenging problem. While drug-dependent treatment for the early stage calcification could slow down its progression, heart valve replacement is inevitable in the late stages. Currently, heart valve replacements involve mainly two types of substitutes: mechanical and biological heart valves. Despite their significant advantages in restoring the cardiac functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 113 publications
0
15
0
Order By: Relevance
“…A relationship between inflammation and calcification has been demonstrated in many studies (3,5). Macrophage is the most found immune cell in BHVs, whereas T lymphocytes and B lymphocytes, neutrophils, and eosinophils are less frequent.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…A relationship between inflammation and calcification has been demonstrated in many studies (3,5). Macrophage is the most found immune cell in BHVs, whereas T lymphocytes and B lymphocytes, neutrophils, and eosinophils are less frequent.…”
Section: Discussionmentioning
confidence: 89%
“…Our study showed that sevelamer does not affect body weight and food intake, corroborating previous studies ( 13 ). Bone parameters were not measured in this study, but according to the literature, sevelamer cannot reduce bone density ( 5 , 14 ). Since sevelamer cannot be absorbed in the gut and cannot induce hypophosphatemia and hypocalcemia, we can conclude that sevelamer is a safe treatment to attenuate BHV calcification.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations